Stem bark of Canarium odontophyllum Miq. (Dabai) as potential source of antimicrobial agent - Dayang Fredalina Basri,; Noor Fazdilah Mustari,; Zafira Ayushah Zainul Alamin,; Noraziah Mohammad Zin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The objective of this study was to evaluate the antimicrobial potential of methanol, acetone and distilled water stem bark extracts from Canarium odontophyllum against Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 6633, Escherichia coli ATCC 25932, Pseudomonas aeruginosa ATCC 27853, Acinetobacter baumannii strain sensitive, Candida albicans ATCC 64677, Candida glabrata ATCC 90028, Aspergillus niger and Fusarium solani M2781. The extracts from C. odontophyllum stem bark from 3.125 mg/ml to 25 mg/ml were screened against the tested microorganisms using disc diffusion method. The Minimum inhibitory concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the extracts against susceptible organisms were determined using microbroth dilution method and streak-plate technique, respectively. From the antibacterial screening assay, the growth of S. aureus, B. cereus and A. baumannii were inhibited by methanol extract whereas the acetone extract was capable of inhibiting all the tested microorganisms except E.coli, F. solani and A. niger. The lowest MIC value for methanol extract was against A. baumannii (0.195 mg/ml) whereas its MBC value was twice its MIC value (0.391 mg/ml), indicating that methanol extract was bacteriostatic against A. baumannii. While for acetone extract, S. aureus showed bactericidal effect with equal MIC and MBC values at 0.195 mg/ml. In conclusion, stem bark of C. odontophyllum has the potential to be the source of antibacterial agent and can be exploited as an alternative phytoantimicrobial.